2014
DOI: 10.1002/2013gc005186
|View full text |Cite
|
Sign up to set email alerts
|

Constraining melt geometries beneath the Afar Depression, Ethiopia from teleseismic receiver functions: The anisotropic H‐κstacking technique

Abstract: Understanding the nature of the crust has long been a goal for seismologists when imaging the Earth. This is particularly true in volcanic regions where imaging melt storage and migration can have important implications for the size and nature of an eruption. Receiver functions and the H-j stacking (Hj) technique are often used to constrain crustal thickness (H) and the ratio of P to S wave velocities (j). In this paper, I show that it is essential to consider anisotropy when performing Hj. I show that in a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 66 publications
(100 reference statements)
6
69
0
Order By: Relevance
“…We compare to the Vs structure of the southeastern plateau, least modified by rifting. We estimate ~3% melt for the MER, within the range of ~0.5–5% from previous seismic studies (Gallacher et al, ; Guidarelli et al, ; Hammond, ). However, models from magnetotelluric and gravity studies yield higher melt fractions of 3–20% (Cornwell et al, ; Keranen et al, ; Whaler & Hautot, ).…”
Section: Discussionsupporting
confidence: 70%
“…We compare to the Vs structure of the southeastern plateau, least modified by rifting. We estimate ~3% melt for the MER, within the range of ~0.5–5% from previous seismic studies (Gallacher et al, ; Guidarelli et al, ; Hammond, ). However, models from magnetotelluric and gravity studies yield higher melt fractions of 3–20% (Cornwell et al, ; Keranen et al, ; Whaler & Hautot, ).…”
Section: Discussionsupporting
confidence: 70%
“…With water expected to alter the depth of the 520, it is plausible that the variability in depth is also related to water content [Inoue et al, 2010]. A recent study of the 520 beneath the African continent, incorporating data from station ATD, also attests to the variability of this discontinuity beneath our study region [Juli a and Nyblade, 2013].…”
Section: Discussionmentioning
confidence: 59%
“…There is extensive evidence, from Interferometric Synthetic Aperture Radar, magnetics, receiver functions, magnetotellurics, and seismic anisotropy for the presence of dikes and sills in the crust south of 13°N in Afar (Wright et al, 2006;Keir et al, 2011;Bridges et al, 2012;Desissa et al, 2013;Hammond, 2014). Furthermore, a study into 40 years of seismicity in Afar by Hofstetter and Beyth (2003) found that > 50% of the geodetic moment, as predicted by plate separation rates, is taken up aseismically.…”
Section: Geological Settingmentioning
confidence: 99%